An Integrated Antenna System for 4G and Millimeter-Wave 5G Future Handheld Devices - Naqvi SI; Naqvi AH; Arshad F; Riaz MA; Azam MA; Khan MS; Amin Y; Loo J; Tenhunen H (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2022)
In this work, an integrated antenna system with Defected Ground Structure (DGS) is presented for Fourth Generation (4G) and millimeter (mm)-wave Fifth Generation (5G) wireless applications and handheld devices. The proposed design with overall dimensions of 110 mm x 75 mm is modeled on 0.508 mm thick Rogers RT/Duroid 5880 substrate. Radiating structure consists of antenna arrays excited by the T-shape 1 x 2 power divider/combiner. Dual bands for 4G centered at 3.8 GHz and 5.5 GHz are attained, whereas the 10-dB impedance bandwidth of 24.4 - 29.3 GHz is achieved for the 5G antenna array. In addition, a peak gain of 5.41 dBi is demonstrated across the operating bandwidth of the 4G antenna array. Similarly, for the 5G mm-wave configuration the attained peak gain is 10.29 dBi. Moreover, significant isolation is obtained between the two antenna modules ensuring efficient dual-frequency band operation using a single integrated solution. To endorse the concept, antenna prototype is fabricated and far-field measurements are procured. Simulated and measured results exhibit coherence. Also the proposed design is investigated for the beam steering capability of the mm-wave 5G antenna array using CST(R)MWS(R). The demonstrated structure offers various advantages including compactness, wide bandwidth, high gain, and planar configuration. Hence, the attained radiation characteristics prove the suitability of the proposed design for the current and future wireless handheld devices.